2021
DOI: 10.9734/ajarr/2021/v15i230366
|View full text |Cite
|
Sign up to set email alerts
|

Locus of Control and Self Esteem as Correlates of Secondary School Students Academic Achievement in English Language in Anambra State

Abstract: Aims: The failure rate in English language subjects as consistently been recorded in major examinations in the country makes it a worrisome situation. This is such that the schools are gradually losing its reputation which could likely result in loss of confidence in the students. Hence, this study aims at determining the relationship among locus of control, self-esteem and secondary school students’ academic achievement in English language. Study Design: The study adopted the correlation design. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Meanwhile, according to Arslan & Akin in Munawir et al, (2018) external locus of control is an individual's belief that fate is determined by external factors. The individual view events that arise as coming from factors or forces outside of control such as luck, misfortune, destiny, and opportunity (Akunne & Anyamene, 2021). Beck in Muazzam et al, (2023) showed findings that there is a relationship between locus of control and academic procrastination that internal locus of control is associated with a lower tendency to procrastinate, and vice versa, external locus of control is associated with a higher tendency to procrastinate tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, according to Arslan & Akin in Munawir et al, (2018) external locus of control is an individual's belief that fate is determined by external factors. The individual view events that arise as coming from factors or forces outside of control such as luck, misfortune, destiny, and opportunity (Akunne & Anyamene, 2021). Beck in Muazzam et al, (2023) showed findings that there is a relationship between locus of control and academic procrastination that internal locus of control is associated with a lower tendency to procrastinate, and vice versa, external locus of control is associated with a higher tendency to procrastinate tasks.…”
Section: Introductionmentioning
confidence: 99%